Generationenromane als politische Entwicklungsromane? Zwei Annäherungsversuche an die ideologische Erbschaft - Erzsébet (FILOGI, 2020)
Can family novels function as a medium describing political transformation processes in young adult’s mental development? With two contemporary novels from Austrian and Hungarian authors this work focuses on the relation between political socialization and political interest in family narratives. What role does family and society play when young men have to face the past, is their philosophy of life determined by the history?